MP55: Characteristics associated with biphasic reactions in an adult population. (May 2019) - Lachance, A.; Ben-shoshan, M.; Cournoyer, A.; Daoust, R.; La Vieille, S.; Huard, V.; Lessard, J.; Paquet, J.; Marquis, M.; Gabrielli, S.; Shand, G.; Morris, J.
Abstract : Introduction : Biphasic anaphylactic reactions are a concern in emergency medicine. Risk factors associated with this type of reaction remain ill-defined. The aim of this study was to investigate elements associated with biphasic anaphylactic reactions and to determine the impact of anaphylaxis treatments on biphasic reactions.Methods : From the multicenter Cross-Canada Anaphylaxis Registry prospective cohort, we selected adults (≥18 years) with a visit to the emergency department (ED) of Sacré-Cœur Hospital, an urban tertiary-care hospital. Then, a structured chart review was done to collect additional information on types and timing of treatments for the initial anaphylactic reaction, presence and treatment of biphasic reactions during the initial ED visit or upon patients' return. Biphasic reactions were defined by the recurrence of any anaphylaxis symptoms within 72 hours of a resolved anaphylaxis episode. Potential factors associated with biphasic reactions were studied using Chi-Square and Mann-Whitney tests.Results : Patients with anaphylaxis were enrolled between April 2014 and February 2018. From the cohort, 401 adult patients were identified. We found 37 patients who developed a biphasic reaction. Amongst them, 33 received treatments and 9 required more than one dose of intramuscular epinephrine. None of the biphasic reaction patients required intravenous epinephrine, other vasopressors, ICU admission, or endotracheal intubation. Biphasic reactions appeared in a median time of 13.3h after the initial reaction ranging from 1.1h to 69.6h (IQR 30.2). There was no difference in age or gender of patients who developed a biphasic reaction compared those who did not. Pertinent past medical history, daily medications, mean of arrival to the ED, allergen type, ingestion route, or initial symptoms during the anaphylaxis episode were not significantly different in the two groups. Treatment with corticosteroids was similar in the two groups (9.0% vs. 8.1% p = 0.82). Treatment, dose and route of administration of epinephrine was not different in the two groups but longer delays before treatment with the first dose of epinephrine was more frequent in biphasic reaction patients (median delay of 64 minutes, p = 0.015).Conclusion : No patient characteristic, allergen, route of ingestion, symptom, nor treatment with corticosteroids has shown to be significantly different in patients with and without biphasic reactions. Delayed treatment with epinephrine is significantly associated with biphasic reactions.